DAMPAK PENERAPAN E-MATERAI TERHADAP PENDAPATAN KANTOR POS CABANG NGAWI - Fitrianti, Ratna; Anifah, Siti (Fakultas Ekonomi Bisnis Islam, 2025)
This study aims to analyze the impact of the implementation of e-stamps on the income of the Ngawi Branch Post Office. In the era of digitalization, innovations such as e-stamps are expected to improve operational efficiency and provide convenience for customers in conducting administrative transactions. The research method used is a quantitative approach with a descriptive and causal design, where data is collected through questionnaires and secondary data analysis from post office financial reports. The results of the study indicate that there is a significant increase in income after the implementation of e-stamps. Efficiency in the administrative process and ease of access for customers are the main factors that drive increased income. In addition, the success of the implementation of e-stamps is also influenced by socialization, infrastructure availability, and management support. This study contributes to the understanding of public service innovation and its implications for economic performance, and offers recommendations for policy development in the postal service sector in Indonesia.